Ocorrência de fungos endofíticos radiculares com potencial antagônico a três biovares de ralstonia solanacearum - Nogueira, Lucinaia Bentes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The endophytic fungi inhabit an ecological niche similar to that occupied by plant pathogens, and thus can be used as their biological control agents through competition for nutrients, production of antagonistic substances, parasitizing the pathogen or inducing plant resistance. Ralstonia solanacearum is a plant pathogen that attacks some plant species of agricultural importance, mainly in tropical regions. The purpose of this study was to evaluate the potential antagonistic of 51 endophytic fungi root isolated from plants of two Agroforestry System against three biovars of Ralstonia solanacearum and estimate the minimum inhibitory concentration of fungal extracts. To evaluate the antagonistic potential of endophytic fungi was disk diffusion paper. The evaluations were performed 24h after mounting the experiment by measuring the inhibition zone. The fungi that showed inhibition zone were tested using broth micro dilution in different concentrations of fungal extract. Of the 51 root endophytic fungi tested, ten showed antagonistic potential against at least one of the three biovars of R. solanacearum. Among the ten endophytic fungi, five (INPA FE 001, INPA FE 004, INPA FE 005, INPA FE 007 and INPA FE 008) showed potential to control the three biovars. The biovar II of R. solanacearum, among the three tested, was the most inhibited by the fungal extracts. Among the two periods of getting fungal extracts, those obtained after 16 days of fungal growth showed the best results (inhibition). The lowest dilution of extract obtained which inhibited fungal bacterial growth was 25% of the INPA FE 001 and INPA 007 for biovar I, 12.5% of INPA FE 007 for biovar II and 25% of the EF INPA 002 to biovar III.
Keywords: Ecologia microbiana; Antagonismo microbiano; Extrato fúngico